Endoscopic Treatment of Subepithelial Tumors - Su Young Kim; Kyoung-Oh Kim (Korean Society of Gastrointestinal Endoscopy, 2018)
Gastrointestinal subepithelial tumors (SETs) are generally found during endoscopy and their incidence has gradually increased. Although the indications for the endoscopic treatment of patients with SETs remain to be established, the feasibility and safety of endoscopic dissection, including the advantages of this method compared with surgical treatment, have been validated in many studies. The development of endoscopic techniques, such as endoscopic submucosal dissection, endoscopic enucleation, endoscopic excavation, endoscopic submucosal tunnel dissection, submucosal tunnel endoscopic resection, and endoscopic full-thickness resection has enabled the removal of SETs while reducing the occurrence of complications. Here, we discuss the endoscopic treatment of patients with SETs, outcomes for endoscopic treatment, and procedure-related complications. We also consider the advantages and disadvantages of the various endoscopic techniques.